2018
DOI: 10.3390/ijms19124048
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Utilization of Bergamottin, Derived from Grapefruits, in Cancer Prevention and Therapy

Abstract: Cancer still remains one of the leading causes of death worldwide. In spite of significant advances in treatment options and the advent of novel targeted therapies, there still remains an unmet need for the identification of novel pharmacological agents for cancer therapy. This has led to several studies evaluating the possible application of natural agents found in vegetables, fruits, or plant-derived products that may be useful for cancer treatment. Bergamottin is a furanocoumarin derived from grapefruits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 98 publications
2
27
0
Order By: Relevance
“…Angelicin inhibits A549 non-small-cell lung carcinoma (NSCLC) growth and metastasis by reducing MMP-2,9; increasing E-cadherin expression levels and JNK, and ERK activation [33]. Bergamottin inhibited the migration abilities of A549, H1299 [34]; HT-1080 cells [35] and human fibrosarcoma HT-1080 cells [36], by decreasing the phorbol 12-myristate 13-acetate (PMA)-initiated enactment of matrix metallo proteinase (MMP)-2,9; c-jun N-terminal kinase (JNK) phosphorylation and EMT inhibition through NF-κB inactivation. Psoralen give similar response in MCF-7/ADR cells [37].…”
Section: Nf-κb Inactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Angelicin inhibits A549 non-small-cell lung carcinoma (NSCLC) growth and metastasis by reducing MMP-2,9; increasing E-cadherin expression levels and JNK, and ERK activation [33]. Bergamottin inhibited the migration abilities of A549, H1299 [34]; HT-1080 cells [35] and human fibrosarcoma HT-1080 cells [36], by decreasing the phorbol 12-myristate 13-acetate (PMA)-initiated enactment of matrix metallo proteinase (MMP)-2,9; c-jun N-terminal kinase (JNK) phosphorylation and EMT inhibition through NF-κB inactivation. Psoralen give similar response in MCF-7/ADR cells [37].…”
Section: Nf-κb Inactivationmentioning
confidence: 99%
“…Imperatorin reduced IL-6, -1β, and TNF-α discharge and inhibited iNOS and COX-2 by repressing NF-κB in RAW 264.7 (murine-macrophages-cell lines) [45,46]. Bergamottin, Bergapten and Psoralen inhibit ROS/NO generation for anti-inflammatory activity [35,47,48].…”
Section: Nf-κb Inactivationmentioning
confidence: 99%
“…Large scale production, low cost and the aroma characteristic remaining are the big advantages of the cold-pressing method. However, cold-pressed grapefruit oil contains waxes, pesticide residues, coumarins, carotenoids and other nonvolatile components [28][29][30], some of them also have good bioactivities that may cause bias in bioactivity research of EO. César et al (2009) found that furanocoumarins isolated from grapefruit peel oil showed potent in vitro inhibitory activity against intestinal cytochrome P450 3A4, an enzyme involved in "grapefruit/drug" interactions in humans [28].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that metastases, i.e. cancer cells that spread from their site of origin to distant organs and initiate the formation of secondary tumors, are responsible for around 90% of mortality in cancer patients 1 . Hence, metastasis is both a critical measure of cancer severity and an important target for cancer therapy.…”
mentioning
confidence: 99%